Effects of active microbreaks on the physical and mental well-being of office workers: A systematic review. Issue 1 (31st December 2022) - Radwan, Ahnmed; Barnes, Luke; DeResh, Renee; Englund, Christian; Gribanoff, Sara
Abstract: Risk factors associated with sedentary work and prolonged sitting time can be detrimental to office workers' health and productivity. Recent literature introduced the concept of active microbreaks and their benefits to sedentary workers. The purpose of this study was to better define active microbreaks and to determine the evidence behind utilizing active microbreaks at work, through a qualitative synthesis of the literature in a systematic review. A comprehensive systematic search was conducted using primarily ergonomics, medicine and allied health databases, in addition to grey literature (CINAHL, Google Scholar, PubMed, and ScienceDirect) and respective ergonomics journals. Six interventional controlled trials (232 total participants) met the inclusion criteria and qualified for the inclusion in this review. The quality of the reviewed articles was deemed to be moderate to high according to the utilized assessment scales. The results of this review may support the use of short active microbreaks (2–3 minutes of light intensity exercises every 30 minutes) due to the observed physical and mental health benefits without negative impact on productivity in the workplace.